The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.imr.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Development of electromyographic indicators for the diagnosis of temporomandibular disorders: a protocol for an assessor-blinded cross-sectional study

Abstract: BackgroundNoninvasive and easy-to-use surface electromyography (EMG) is frequently utilized for the diagnosis of temporomandibular disorders (TMDs). However, few EMG parameters that consider TMDs in addition to the cranio-cervical-mandibular system have been regarded as important in traditional Korean medicine.MethodsThis clinical trial will be conducted as an assessor-blinded cross-sectional study. The participants will be classified based on the Diagnostic Criteria for TMDs Symptom Questionnaire (DC/TMD SQ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…However, methodological difficulties related to the standardization of the technique have proven difficult to overcome, and several methods have been clinically impracticable (21) . The validity, sensitivity, and specificity of the records with the variables analyzed so far (latency, morphology, and electromyographic silent period) have been questioned based on current scientific evidence (22)(23)(24)(25)(26) .…”
Section: Discussionmentioning
confidence: 99%
“…However, methodological difficulties related to the standardization of the technique have proven difficult to overcome, and several methods have been clinically impracticable (21) . The validity, sensitivity, and specificity of the records with the variables analyzed so far (latency, morphology, and electromyographic silent period) have been questioned based on current scientific evidence (22)(23)(24)(25)(26) .…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies suggested that SEMG is a useful objective tool for diagnosis of the dysfunction of the masticatory muscles in patients with TMDs 15,2224 , while other studies contradict this opinion and stated that SEMG has limited role in TMDs diagnosis and could leads to a unnecessary dental treatment to treat these disorders 2527 , in between these two opposite opinions, recent studies mentioned that SEMG can be used only as a complementary tool for the diagnosis of the myogenous TMDs 17 .…”
Section: Discussionmentioning
confidence: 99%
“…This clinical symptoms are still considered by many as a subjective tool for assessment. It has been reported that a need for objective data in decision making is necessary to reduce reliance on subjective improvement and clinically observed data 15,16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnostics of temporomandibular disorders can be extended with computed tomography, magnetic resonance imaging, or X-ray imaging. Nonetheless, these methods are hard to reach, expensive, and limited in the assessment of clinical symptoms of TMDs [9]. Other examinations used in diagnostics of TMDs are mandibular kinesiography (MKG), ultrasonography, and electromyography (EMG) [10].…”
Section: Introductionmentioning
confidence: 99%